2010
DOI: 10.1007/s00405-010-1416-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of differentiated thyroid cancer in South East England: 1987–2006

Abstract: There has been a worldwide increase in the incidence of thyroid cancer (TC). Documenting these recent trends is of immense value to cancer control measures, monitoring policies, improving clinical outcomes, resource allocation and stimulating research. Hence this study aimed to analyse the changes in incidence, staging and morphologic types of TC in South East England (1987-2006) by means of a retrospective, descriptive epidemiological study using anonymized data obtained from the Thames Cancer Registry (TCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 35 publications
2
33
1
2
Order By: Relevance
“…A substantial accumulation of evidence has shown that age-adjusted incidence of thyroid cancer has increased worldwide for many decades (1)(2)(3)(4)(5)(6)(7). This trend started as early as 1940 and has steadily increased since that time (8).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial accumulation of evidence has shown that age-adjusted incidence of thyroid cancer has increased worldwide for many decades (1)(2)(3)(4)(5)(6)(7). This trend started as early as 1940 and has steadily increased since that time (8).…”
Section: Introductionmentioning
confidence: 99%
“…TC is commonly diagnosed at a younger age than the majority of other adult cancers (2). The 4 main histological types of TC are papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC), medullary thyroid carcinoma (MTC) and anaplastic (undifferentiated) carcinoma (ATC) (3,4). PTC and FTC constitute approximately 90% of total number of TC cases and are treatable and usually curable.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for these increasing incidence rates is not only explained by early detection from increased health screening with high-resolution ultrasonography (17)(18)(19), but may also be associated with environmental changes or radiation exposure (20)(21)(22). In Korea, the incidence of thyroid cancer is also rapidly increasing; the incidence rates per 100,000 persons adjusting for age increased from 2.1 (in 1999) to 15.4 (in 2009) in males and 10.4 (in 1999) to 79.6 (in 2009) in females (23)-rates that are higher than in any other country studied (24).…”
mentioning
confidence: 99%